Pengembangan Media Pembelajaran Interaktif Berbasis Augmented Reality untuk Klasifikasi Hewan Vertebrata dan Invertebrata Menggunakan Metode GDLC - Muhammad Iqbal Hidayahtullah; Sigit Sugiyanto; Tito Pinandita; Dimara Kusuma Hakim (Sekawan Institut, 2025)
This study introduces an innovative Augmented Reality (AR)-based learning media for teaching ani-mal classification, specifically visualizing vertebrates and invertebrates in interactive three-dimensional form. Developed using Unity 3D and Vuforia with the Game Development Life Cy-cle (GDLC) waterfall model, the application offers an engaging learning experience through mark-er-based scanning that displays 3D animal objects, instructional materials, and evaluative quizzes. The novelty of this research lies in the integration of 3D visualization and interactive learning that enables students to explore and test their understanding in real time. Functional testing using the Black Box method confirmed that all features operated correctly, while field trials involving 20 students from SD Negeri Karanggintung 04 showed a high satisfaction rate of 88.75% (strongly agree category). Fur-thermore, post-test results demonstrated a significant improvement compared to pre-test scores, with students’ performance increasing from the 2–3 range to 4–5. With its visual and interactive approach, this AR-based learning media effectively enhances student comprehension and engagement, offering a promising and innovative solution for biology education at the elementary level.